Left ventricular function in type 2 diabetics - Y. Hussain, Fakher (Tikrit Journal of Pharmaceutical Sciences, 2023)
Diabetic cardiomyopathy has been proposed as an independent cardiovascular disease and many mechanisms, such as microvascular disease, autonomic dysfunction, metabolic disorders, and interstitial fibrosis, have been suggested as causative factors. However, the exact causes and mechanisms of diabetic cardiomyopathy remain unclear. Several studies have demonstrated evidence for preclinical left ventricular (LV) diastolic dysfunction in patients with diabetes mellitus (DM) independent of coronary disease or hypertension. The prevalence of diastolic dysfunction in asymptomatic patients with type 2 diabetes mellitus or its relation with other diabetic complications (nephropathy, retinopathy, and neuropathy) is not well defined and data are controversial. A case series study of ninety patients with type 2 diabetes mellitus was designed to determine the frequency of asymptomatic left ventricular diastolic dysfunction in type 2 diabetes patients and its relation to patients’ duration, control of diabetes and other factors, the setting was at Diabetes Clinic, Echocardiography Unit and wards of Ibn Sina Teaching Hospital. During the period from the 1st of July to 31st of December 2011, eighty seven consecutive normotensive diabetic patients type 2 (mean age 51.35+8.21 years) and having no coronary artery disease on non invasive testing, were studied for assessment of left ventricular diastolic function using pulsed Doppler at the tip of mitral valve, the peak late (atrial) transmitral flow velocity (A wave), the peak early transmitral flow velocity (E wave),the (E wave) deceleration time and the ratio between (E wave) and (A wave) were assessed. Tissue Doppler was also used to assess the basal septal (medial) mitral valve annular velocities, the peak early basal annular velocity ( E` wave ) and the peak late basal annular velocity (A` wave) in addition E/E` ratio was assessed, left ventricular diastolic function was classified as left ventricular diastolic dysfunction positive and left ventricular diastolic dysfunction negative, further classification in to normal, impaired relaxation and Pseudonormal groups was made, age gender duration of diabetes, atherogenic index, obesity were studied in relation to left ventricular diastolic dysfunction using Chi square and Fissures exact tests, T-tests and ANOVA were used to calculate means and to compare them.